1968
DOI: 10.1266/jjg.43.89
|View full text |Cite
|
Sign up to set email alerts
|

Possible Mutagenic Hazards of Some Food Additives, Beverages and Insecticides

Abstract: It has long been known that radiomimetic chemical agents which produce chromosome aberrations in plant and animal cells may also produce mutations.The early discovery by Kihlman and Levan (1949) that caffeine induces aberrations in plant chromosomes and the more recent report by Ostertag (1966) that caffeine breaks human chromosomes has led to further tests of the radiomimetic effect of beverages, food additives and home insecticides. Agents which break plant chromosomes may not break animal chromosomes, but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1972
1972
1989
1989

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…since the discovery of Kihlman and Levan (1949) that caffeine induces chromosomal aberrations in plant cells. Sax and Sax (1968) in their studies on the radiomimetic effects of 'Sucaryl' have pointed out that high concentrations of 'Sucaryl' or "Saccharin" were radiomimetic. Antioxidants added to dry cereals, potato chips and other food products to preserve crispness have also been reported to possess chromosome breaking ability.…”
Section: Observationsmentioning
confidence: 99%
See 3 more Smart Citations
“…since the discovery of Kihlman and Levan (1949) that caffeine induces chromosomal aberrations in plant cells. Sax and Sax (1968) in their studies on the radiomimetic effects of 'Sucaryl' have pointed out that high concentrations of 'Sucaryl' or "Saccharin" were radiomimetic. Antioxidants added to dry cereals, potato chips and other food products to preserve crispness have also been reported to possess chromosome breaking ability.…”
Section: Observationsmentioning
confidence: 99%
“…Antioxidants added to dry cereals, potato chips and other food products to preserve crispness have also been reported to possess chromosome breaking ability. The antioxidant BHT (Butylated hydroxytoluene) has been found to break chromosomes and also induce amitotic divisions and polyploidy (Sax and Sax 1968). Swaminathan andNatara jan (1956, 1959) have reported that a few vegetable oils and edible fats are mutagenic.…”
Section: Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research papers on the genetic effects of organophosphorus compounds in insects are not numerous, probably because of the high toxicity of these compounds. Sax and Sax, 1968 (not precise) Sex-linked lethal mutations (in the Muller-5 test) were induced by Trichlorfon, Fenitrothion, and Bromophos after sublethal injections (Benes and Sram, 1969), which makes it difficult to compare the results with mammalian data. Oxydemetonmethyl gave different results according to the insecticide sensitivity of the strain used.…”
Section: 22h Higher Plantsmentioning
confidence: 99%